Effective Criteria For Successful Physical Fitness Testing In Selecting Young Talented Football Players - Ermatov Sherzod Saidovich; Associate Professor, Sharof Rashidov (Zien Journals, 2025)
This article discusses the role of effective test criteria in testing the level of physical fitness of young talented football players, their reliability and informativeness, and the analytical issues of the importance of scientific and theoretical approaches to testing, which is one of the current issues in football today
Keywords: football training; young players; physical training